Effects Of Papaya Leaf Meal, Pineapple Skin Meal And Vitamin D3 Supplements On Meat Quality Of Spent Layer Hens - Navid, Saeid (2010)

(untitled)
A study was conducted to evaluate the effects of supplementation of vitamin D3, papaya leaf meal (PLM) and pineapple skin meal (PSM) for 7 days prior to slaughter on meat quality of spent layer chickens. In Experiment 1, based on Completely Randomized Design, 40 spent layer chickens (ISA Brown) were allotted to control (n=10), vitamin D3 (n=10), papaya leaf meal (n=10) and pineapple skin meal (n=10) treatments. The combined effects of vitamin D3 and PLM were also examined in this study based on 2×4 factorial design of which, 80 ISA Brown spent layer hens were equally divided to PLM with vitamin D3 (n=40) and PLM without vitamin D3 (n=40). Ten birds of each of the main treatment group (PLM with vitamin D3 and PLM without vitamin D3) were then subjected to the levels of 0%, 0.5%, 1% and 2% of PLM. Meat quality analysis (shear force values, drip loss, cooking loss and colour) were carried out for both experiments. In Experiment 1, both vitamin D3 and PLM have significantly improved tenderness (reduced shear force values), drip loss, cooking loss and colour. However, the supplementation of PSM has resulted in no significant effect on all of the analysed meat quality traits. Meanwhile, the results from Experiment 2 demonstrated that PLM without the inclusion of vitamin D3 has significantly improved meat tenderness, cooking loss and colour. In general, the study has highlighted the potential benefits of PLM and vitamin D3 supplementation for improving meat quality in spent chicken.